2010
DOI: 10.1007/s12064-010-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic senescence and semelparity in the Penna aging model

Abstract: The catastrophic senescence of the Pacific salmon is among the initial tests used to validate the Penna aging model. Based on the mutation accumulation theory, the sudden decrease in fitness following reproduction may be solely attributed to the semelparity of the species. In this work, we report other consequences of mutation accumulation. Contrary to earlier findings, such dramatic manifestation of aging depends not only on the choice of breeding strategy but also on the value of the reproduction age, R, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…There are important consequences for adopting the continuous conception of parity as a starting point for modeling the evolution of different modes of parity. Mathematical models based on the discrete conception of parity often predict threshold values-in mortality rate, size at initiation of reproduction, or expected growth rate-that do not agree with empirical observation (Lessells, 2005;Omielan, 1991;Piñol & Banzon, 2011;Su & Peterman, 2012;Trumbo, 2013;Vaupel, Missov, and Metcalf, 2013). In particular, ESS models derived from assumptions rooted in the discrete conception of parity frequently underestimate the adaptive value of semelparous reproductive strategies; even after accounting for the effects of environmental stochasticity and density dependence, ESS models predict that semelparous strategies should be less abundant-and less fit-than they have been found to be (Benton & Grant, 1999).…”
Section: Empirical Support For the Continuous Conception Of Paritymentioning
confidence: 99%
See 1 more Smart Citation
“…There are important consequences for adopting the continuous conception of parity as a starting point for modeling the evolution of different modes of parity. Mathematical models based on the discrete conception of parity often predict threshold values-in mortality rate, size at initiation of reproduction, or expected growth rate-that do not agree with empirical observation (Lessells, 2005;Omielan, 1991;Piñol & Banzon, 2011;Su & Peterman, 2012;Trumbo, 2013;Vaupel, Missov, and Metcalf, 2013). In particular, ESS models derived from assumptions rooted in the discrete conception of parity frequently underestimate the adaptive value of semelparous reproductive strategies; even after accounting for the effects of environmental stochasticity and density dependence, ESS models predict that semelparous strategies should be less abundant-and less fit-than they have been found to be (Benton & Grant, 1999).…”
Section: Empirical Support For the Continuous Conception Of Paritymentioning
confidence: 99%
“…Early conceptual and mathematical models of optimal semelparous reproduction were generally simple and deterministic and were designed to predict a single “threshold” value that optimized life‐history characters such as size at first reproduction (Bell, ; Young, ). Threshold models of this type include senescence‐threshold models based on the Penna aging model (Piñol & Banzon, ), as well as development‐threshold models such as age‐structured life‐history models. Age‐structured models treat age at reproduction, and hence parity, as a discrete variable, and assess the evolutionary consequences of the degree of overlap between juvenile (i.e., prereproductive) and adult (reproductive) classes in a population (Wikan, ).…”
Section: Understanding the Evolution Of Parity As A Continuous Traitmentioning
confidence: 99%
“…For semelparous species, all bits above age R are set to one. In [25], we have demonstrated that this is not always the case. As T increases, the strength of selection decreases and more mutations are preserved in the genome.…”
Section: Nonzero Steady Statesmentioning
confidence: 86%
“…There are important consequences for adopting the continuous conception of parity as a starting point for modeling the evolution of different modes of parity. Mathematical models based on the discrete conception of parity often predict threshold values-in mortality rate, size at initiation of reproduction, or expected growth rate-that do not agree with empirical observation (Lessells, 2005;Omielan, 1991;Piñol & Banzon, 2011;Su & Peterman, 2012;Trumbo, 2013;Vaupel, Missov, and Metcalf, 2013). In particular, ESS models derived from assumptions rooted in the discrete conception of parity frequently underestimate the adaptive value of semelparous reproductive strategies;…”
Section: Empirical Support For the Continuous Conception Of Paritymentioning
confidence: 99%